Similar patterns of rDNA evolution in synthetic and recently formed natural populations of Tragopogon (Asteraceae) allotetraploids - Malinska, Hana; Tate, Jennifer A; Matyasek, Roman; Leitch, Andrew R; Soltis, Douglas E; Soltis, Pamela S; Kovarik, Ales (BMC evolutionary biology, 2010)
BACKGROUND: Tragopogon mirus and T. miscellus are allotetraploids (2n = 24) that formed repeatedly during the past 80 years in eastern Washington and adjacent Idaho (USA) following the introduction of the diploids T. dubius, T. porrifolius, and T. pratensis (2n = 12) from Europe. In most natural populations of T. mirus and T. miscellus, there are far fewer 35S rRNA genes (rDNA) of T. dubius than there are of the other diploid parent (T. porrifolius or T. pratensis). We studied the inheritance of parental rDNA loci in allotetraploids resynthesized from diploid accessions. We investigate the dynamics and directionality of these rDNA losses, as well as the contribution of gene copy number variation in the parental diploids to rDNA variation in the derived tetraploids. RESULTS: Using Southern blot hybridization and fluorescent in situ hybridization (FISH), we analyzed copy numbers and distribution of these highly reiterated genes in seven lines of synthetic T. mirus (110 individuals) and four lines of synthetic T. miscellus (71 individuals). Variation among diploid parents accounted for most of the observed gene imbalances detected in F1 hybrids but cannot explain frequent deviations from repeat additivity seen in the allotetraploid lines. Polyploid lineages involving the same diploid parents differed in rDNA genotype, indicating that conditions immediately following genome doubling are crucial for rDNA changes. About 19% of the resynthesized allotetraploid individuals had equal rDNA contributions from the diploid parents, 74% were skewed towards either T. porrifolius or T. pratensis-type units, and only 7% had more rDNA copies of T. dubius-origin compared to the other two parents. Similar genotype frequencies were observed among natural populations. Despite directional reduction of units, the additivity of 35S rDNA locus number is maintained in 82% of the synthetic lines and in all natural allotetraploids. CONCLUSIONS: Uniparental reductions of homeologous rRNA gene copies occurred in both synthetic and natural populations of Tragopogon allopolyploids. The extent of these rDNA changes was generally higher in natural populations than in the synthetic lines. We hypothesize that locus-specific and chromosomal changes in early generations of allopolyploids may influence patterns of rDNA evolution in later generations.
Keywords: Diploidy; molekulární evoluce; Hybridization, Genetic; Evolution, Molecular; Blotting, Southern; Asteraceae; hybridizace genetická; tetraploidie; diploidie; ribozomální DNA; Southernův blotting; DNA, Ribosomal; In Situ Hybridization, Fluorescence; hybridizace in situ fluorescenční; Tetraploidy